Hydro-climatological changes and mine water management challenges in Canada under climate change - Wahid Palash; Alice Guimaraes; Mohammad AmirRahmani; Samantha Sam; John Steen; Nadja C Kunz (Environmental Research Letters)
Climate change (CC) is already affecting Canada’s hydrologic cycle, posing challenges for water management in mining operations and increasing associated environmental and social risks. However, there is limited research that quantifies the extent of anticipated CC impacts across Canadian watersheds with active mining. This paper aims to fill that gap by assessing CC impacts on key hydroclimatic variables important for Canada’s mine water management. Baseline conditions were established for six key variables: annual precipitation, 24 h intensity–duration–frequency (IDF) precipitation, 10 d extreme precipitation, annual mean temperature, hydrologic drought index like Standardized Precipitation and Evaporation Index (SPEI), and annual snow depth. Date sources included Environment and Climate Change Canada (ECCC) and Coupled Model Intercomparison Project Phase 5 (CMIP5). Future CC projections were generated using ECCC’s transformation equation for 24 h IDF precipitation, the quantile delta mapping (QDM) method for 10 d extreme precipitation, and downscaled, bias corrected CMIP5 ensemble projections for the remaining variables. The assessment considered two greenhouse emission scenarios (RCP4.5 and RCP8.5), and three future timeframes (2020s, 2050s, 2080s). The study reveals projected temperature increases within the case study watersheds of 2.4 °C–3.5 °C by the 2050s and 3 °C–7 °C by the 2080s under median or 50th percentile (p50) conditions. Annual precipitation is expected to rise by 11%–16% (2050s) and 15%–28% (2080s), with more intense shorter-duration events under p50 conditions. For example, the current 100 year 24 h IDF storm is expected to occur more frequently, decreasing to a 27–49 year return period by the 2050s and a 10–40 year return period by the 2080s. Annual average snow depth is projected to decline by 21%–73% (2050s) and 24%–89% (2080s) under p50 conditions. These findings highlights that water management in Canada’s mining regions is set to face escalating hydrological changes under a changing climate. Effective management strategies are therefore essential to prevent intensified environmental and social risks.